Asset Management and Investor Portfolio Behavior: Theory and Practice - Renwick, Fred B. (Journal of Finance, 1969)
Fred B. Renwick, Asset Management and Investor Portfolio Behavior: Theory and Practice, The Journal of Finance, Vol. 24, No. 2, Papers and Proceedings of the Twenty-Seventh Annual Meeting of the American Finance Association Chicago, Illinois December 28-30, 1968 (May, 1969), pp. 181-206